2022
DOI: 10.3390/biology11071049
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Coilia nasus Gonadal Somatic Cell Line Capable of Sperm Induction In Vitro

Abstract: Coilia nasus is an important economic anadromous migratory fish of the Yangtze River in China. In recent years, overfishing and the deterioration of the ecological environment almost led to the extinction of the wild resources of C.nasus. Thus, there is an urgent need to protect this endangered fish. Recently, cell lines derived from fish have proven a promising tool for studying important aspects of aquaculture. In this study, a stable C. nasus gonadal somatic cell line (CnCSC) was established and characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that in lower vertebrates, spermatogenesis can be performed in vitro. In medaka, coculture of the SG3 cell line with gonadal somatic cells from rainbow trout or Coilia nasus [ 47 ] can induce sperm in vitro [ 16 ]. Recently, the whole spermatogenesis process of mice was reproduced in vitro by combining IPS induction technology and 3D culture technology, and the generated organoids formed a structure similar to seminiferous tubules, in which spermatogenesis was performed and functional sperm was obtained [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that in lower vertebrates, spermatogenesis can be performed in vitro. In medaka, coculture of the SG3 cell line with gonadal somatic cells from rainbow trout or Coilia nasus [ 47 ] can induce sperm in vitro [ 16 ]. Recently, the whole spermatogenesis process of mice was reproduced in vitro by combining IPS induction technology and 3D culture technology, and the generated organoids formed a structure similar to seminiferous tubules, in which spermatogenesis was performed and functional sperm was obtained [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the biological signaling pathways are involved in steroidogenesis to mediate the gonad development of teleost fish, such as estrogen and TGF-β signaling pathway ( Baroiller and Guiguen, 2001 ; Amberg et al, 2013 ). Recently data from taper-tail anchovy showed that several genes involved in the sex differentiation cascade exhibited characteristic expression in both gonadal somatic cell lines cultured in vitro ( Kan et al, 2022 ) and in spermatogonial stem cell lines under long-term in vitro culture conditions ( Gu et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Very little research progress has been made on its artificial breeding [ 17 ]. Up to now, the gonadal somatic cell line CnGSC has been isolated from C. nasus [ 1 ]. In the current research, we successfully established the C. nasus spermatogonial cell line (CnSSC) and investigated the in vitro sperm production capability of CnSSC with gonadal somatic cells induction.…”
Section: Introductionmentioning
confidence: 99%
“…Fish species are the most abundant of all vertebrates, but several are in danger of extinction due to severe population decreases [1]. As a consequence, the conservation Biology 2023, 12, 1175 2 of 12 study of fish germplasm resources is becoming more and more crucial to the preservation of fish in danger.…”
Section: Introductionmentioning
confidence: 99%